Self-assembled polycarbazole microspheres as single-component, white-colour resonant photoemitters. Issue 58 (31st May 2016) - Kushida, Soh; Okabe, Shinnosuke; Dao, Thang D.; Ishii, Satoshi; Nagao, Tadaaki; Saeki, Akinori; Kijima, Masashi; Yamamoto, Yohei
Abstract : Self-assembled polycarbazole microspheres exhibit white-colour whispering gallery mode photoluminescence from the whole visible spectral range. Abstract : Self-assembled polycarbazole (PCz) microspheres exhibit whispering gallery mode photoluminescence (PL), where resonant PL lines appear at the whole visible spectral range. The ultra-wide-range PL results from a partial oxidation of PCz upon strong photoexcitation. The single component micro-photoemitters, preparable using a simple and inexpensive process, are applicable as full-colour, narrow-width light emission sources.